Comparison of quantitative flow ratio (QFR) and instantaneous wave-free ratio (iFR) or resting full-cycle ratio (RFR) during daily routine in the catheterization laboratory. (3rd October 2022) - Antoniadis, M; Stader, J; Ussat, M; Wachter, R; Jurisch, D; Lavall, D; Metze, M; Neef, M; Baum, P; Spies, C; Laufs, U; Lenk, K
Abstract: Background: The prognosis of patients with coronary artery disease (CAD) depends strongly on the hemodynamic relevance of the stenosis. The gold standard is the invasive evaluation of the stenosis using Fractional Flow Reserve (FFR), instantaneous wave-free ratio (iFR) or Resting Full-Cycle Ratio (RFR). The use of invasive procedures remains low due to procedural factors and costs. Quantitative Flow Ratio (QFR) is a novel, software-based method to evaluate the physiology of coronary lesions during cardiac catheterization. Computing a three-dimensional model of the vessel based on two angiographic recordings and analyzing the fluid dynamics of the contrast medium flow, the software computes the FFR. In the setting of clinical studies, it has been demonstrated that QFR is feasible and correlates well with FFR. The aim of this study is to compare feasibility and reliability of QFR with established measurements of the iFR or RFR in daily routine. Methods: Patients with an indication for an invasive coronary angiography and a stenosis of 30 to 90% were simultaneously assessed using QFR and iFR/RFR in a routine setting. The QFR-computation was performed online by a certified expert with QAngio XA 3D 3.2. The following outcome parameters were analyzed: time to result, volume of applicated contrast medium, applicated dose area product, result of the evaluation. The results have been registered for both methods, respectively. Results: 102 coronary arteries were analyzed using QFR and iFR or RFR. QFR shows a good correlation (r=0.753, AUC=0.922) and accuracy (agreement 89.22%, sensitivity 95.83%, specificity 83.33%, PPV 83.64%, NPV 95.74%). The data show that QFR delivers significantly faster results and reduces the procedure related applicated radiation dose from in median 598.8 cGy cm 2 to 306.75 cG ycm 2 (p<0.001). The study shows no significant difference regarding the amount of contrast medium used. Conclusion: QFR has a good diagnostic agreement and can reduce procedure length and applicated radiation dose. Thereby QFR could increase the use of physiologically guided coronary interventions in daily routine. Funding Acknowledgement: Type of funding sources: None.